2022
DOI: 10.1111/mec.16622
|View full text |Cite
|
Sign up to set email alerts
|

Genomic divergence of Stellera chamaejasme through local selection across the Qinghai–Tibet plateau and northern China

Abstract: Understanding how populations diverge and new species arise is a central question in evolutionary biology. “Allopatric” divergence through geographical isolation is considered to be the commonest mechanism generating species biodiversity in mountain ecosystems. However, the underlying genomic dynamics, especially genomic islands of elevated divergence and genes that are highly diverged as a result of lineage‐specific selection, remain poorly understood. Stellera chamaejasme has a wide geographical range across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…Theory and empirical studies support the idea that these islands can form around loci underlying local adaptation and/or reproductive isolation (e.g. Tavares, et al 2018;McCulloch, et al 2020;Hu, et al 2022). Thus, delineating differentiation islands has recently become a major topic of research in the field of speciation and adaptation genomics (Burri 2017b;Martin and Jiggins 2017;Ravinet, et al 2018;Tavares, et al 2018;Stankowski, et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Theory and empirical studies support the idea that these islands can form around loci underlying local adaptation and/or reproductive isolation (e.g. Tavares, et al 2018;McCulloch, et al 2020;Hu, et al 2022). Thus, delineating differentiation islands has recently become a major topic of research in the field of speciation and adaptation genomics (Burri 2017b;Martin and Jiggins 2017;Ravinet, et al 2018;Tavares, et al 2018;Stankowski, et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…There were also obvious differences in the adaptations of O. japonica and O. chinensis to local environmental conditions. Although both the PSGs and CNDGs showed a significant overlapping with the identified islands, the overlap number was small suggesting the selection of non‐island regions may important during their divergence (Hu et al, 2022 ). The functions of PSGs and CNDGs were mainly related to plant development, responses to stimuli, and reproduction (Tables S8 and S11 ), which, being fundamental processes in a plant's life‐cycle, may have been responsible for the reproductive isolation of the two species.…”
Section: Discussionmentioning
confidence: 99%
“…Under the latter scenario, genomic islands derived from divergent selection with gene flow tend to be clustered together. Although numerous studies have revealed that divergent sorting of ancient polymorphism is the major mode in generating genomic islands (e.g., Han et al, 2017;Hu et al, 2022;Ke et al, 2022;Ma et al, 2018), the contribution of gene flow in generating the genomic islands could not be excluded here because of the continuous gene flow and both heterogeneous and clustered distribution of islands observed between the two species. In addition, we found decreased levels of genetic diversity, Tajima's D and recombination rates across genomic islands, and a strong association between islands of divergence and these selection signals (Table S5).…”
Section: Genomic Islands Of Divergence and Ecological Adaptationmentioning
confidence: 99%